Moss mites (Acari: Oribatida) in soil revitalizing: a chance for practical application in silviculture - Klimek, Andrzej; Rolbiecki, Stanisław (Biological Letters, 2015)
The Oribatida (known as moss mites or beetle mites) increase the breakdown of organic material in the soil. The paper analyses the dynamics of their abundance and number of species after various treatments enriching the soil in 4 study areas: afforested post-agricultural area in the Tuchola Forest, afforested degraded post-military training area in Bydgoszcz-Jachcice, and forest nurseries at Białe Błota and Bielawy. The results show that in post-agricultural and degraded soils at the initial stages of forest succession, the density and number of species of oribatid mites were low, even after phyto-land-improvement (afforestation and lupin as green manure). In the forest nurseries, however, we recorded a positive effect of soil revitalizing after mulching with forest ectohumus (i.e. organic surface layer of the soil). The inoculation of soils with forest mesofauna appeared more effective in nursery plantations of silver birch (Betula pendula) and small-leaved lime (Tilia cordata), as compared with Scots pine (Pinus sylvestris). Thus to revitalize degraded soils effectively and to accelerate forest succession, apart from phytoland- improvement, it is advisable also to reintroduce mesofauna, e.g. with the use of forest ectohumus.